Implementasi Nilai Keislaman dalam Upaya Pembentukan Karakter Religius di Panti Asuhan Ridha Muhammadiyah Enrekang - Muh. Iswandi; Yunus Busa; Uli Nuha; Baharuddin; Haerusman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research is motivated by the importance of foster children's religious character formation through the application of Islamic values in the orphanage environment as a religious-based social educational institution. This study aims to determine the implementation of Islamic values, the role of caregivers, and their impact on the formation of religious character in foster children at the Ridha Muhammadiyah Enrekang Orphanage. This study uses a qualitative approach with a descriptive research type. The research was conducted at the Ridha Muhammadiyah Enrekang Orphanage with research subjects including managers, caregivers, foster children, and alumni of the orphanage. Research data were obtained through interviews, observations, and documentation, then analyzed using the Miles and Huberman model through the stages of data condensation, data presentation, and drawing conclusions. The validity of the data was tested through triangulation of sources and techniques. The results of the study indicate that the implementation of Islamic values is carried out through habituation of worship, moral development, providing advice, and exemplary behavior of caregivers. This application has an impact on improving the discipline of worship, responsibility, independence, and social behavior of foster children. The implications of this research indicate that Islamic value-based parenting patterns can be an effective strategy in shaping the religious character of children in social welfare institutions.